Multifold improvement of thermoelectric power factor by tuning bismuth and antimony in nanostructured n-type bismuth antimony telluride thin films. (5th February 2019) - Murmu, Peter P.; Kennedy, John; Suman, Sidharth; Chong, Shen V.; Leveneur, Jérôme; Storey, James; Rubanov, Sergey; Ramanath, Ganpati
Abstract: Bismuth telluride (Bi2 Te3 ) based alloys are preferred thermoelectric materials for room temperature thermoelectric applications. Electrical transport and thermopower properties of n-type nanostructured Bix Sb2-x Te3 films were tuned by post-growth heat treatment. We report that annealing of sputter-deposited nanostructured Bi0.7 Sb1.3 Te3 films lead to several-fold increases in thermoelectric power factor α 2 σ, where σ is electronic conductivity and α is Seebeck coefficient. Annealing at Tanneal = 200 °C nearly quadruples the power factor to α 2 σ = 3.1 μW cm −1 K −2 . Spectroscopy and microscopy analyses indicate that the power factor increase is attributable to 50% decrease in the Bi/Sb ratio, and grain growth, which increase the charge carrier concentration and mobility. The observed Bi depletion is contrary to annealing-induced Te depletion reported in p-type films. For Tanneal > 200 °C, although continued Bi depletion increases σ, a precipitous decrease in α sharply lowers the power factor, yielding tenfold lower α 2 σ for Tanneal = 400 °C than the as-deposited films. Our findings indicate that post-deposition annealing is a potent way to tune the thermoelectric properties of n-type Bi2 Te3 -based alloy films to fabricate devices for high-efficiency solid-state refrigeration and power harvesting from waste heat. Graphical abstract: Unlabelled Image Highlights: Compositional, microstructural and thermoelectric properties of nanostructured n-type bismuth antimony telluride (Bix Sb2-x Te3 ) Multifold enhancement in thermoelectric power factor (PF) in Bix Sb2-x Te3 films PF enhancement correlates with annealing-induced grain growth and Bi depletion. Thermal annealing potent way to improve PF by tuning composition and microstructure